SOLAR INSOLATION ANALYSIS TOOLS FOR RESIDENTIAL BUILDINGS IN HEALTHY LIVING ENVIRONMENT DESIGN (Scientific journal of the Fergana State University, 2025)
This paper provides a short review of current issues on conformance of sanitary and epidemiological rules, energy-efficient building design topics. Discussed the software tools that can be efficiently used during the design process by students, researchers, architects, and designers to improve their understanding of passive house design aspects.